Analisis Efisiensi dan Produktivitas Bank Umum Syariah di Indonesia - Khalimah, Nur; Gunanto, Edy Yusuf Agung (MALIA: Journal of Islamic Banking and Finance, 2022)
The development of Islamic Commercial Banks in Indonesia is still not optimal. It is necessary to measure efficiency and productivity to achieve predetermined targets. This study measures the level of efficiency of 12 Islamic commercial banks in Indonesia for the 2016-2018 period using DEA (Data Envelopment Analysis) and measures the level of productivity using malmquist index. The results show that the overall efficiency of Islamic commercial banks in Indonesia has decreased. The decreased because five Islamic Commercial Banks have not maximized their inputs and outputs so that inefficiency. This inefficiency is accompanied by a decrease in productivity. The results of the malmquist index show productivity in 2016-2017 is better than 2017-2018 with an increase in productivity in 2016-2017 reaching 67% and in 2017-2018 it decreased to 25%. The increase and decrease is dominated by technology companies (frontier shift). This makes technological innovation one that needs attention.